Ecofeminine Consciousness in Sarah Orne Jewett’s “A White Heron” - joshi, Bhup raj (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
The dominating human practices and discourses regarding nature were questioned in 1970s in the USA with the emergence of eco feminism that talks of affinity between female and ecology. It is an academic form of the movement targeting to critique the exploitation of nature by human beings as of the women by men. This paper aims at analyzing close relation between women and nature in Sarah Orne Jewett’ “A White Heron” from eco-feminist perspective. The project is based on the conflict between culture and the nature in the story represented by a male and the females respectively. The discussion will reassert the repressive and submissive; or destructive and protective gender roles over the nature